ASUHAN KEPERAWATAN GERONTIK PASIEN HIPERTENSI GRADE II DENGAN AIR SEDUHAN BAWANG PUTIH - Himawan, Dino; Novia, Resi (Ensiklopedia of Journal, 2025)
Hypertension is a major non-communicable disease and a leading global cause of death, with WHO estimating its prevalence at 22% worldwide. In the Riau Islands Province, the 2024 prevalence among individuals over 60 years reached 44.0%, while in Batam City, 12,230 elderly people at the Lubuk Baja Community Health Center were recorded with hypertension. This Professional Scientific Paper aims to provide geriatric nursing care to Mrs. J, a patient with grade II hypertension, through the administration of garlic water infusion as an alternative therapy to help reduce blood pressure in the Lubuk Baja Community Health Center Working Area, Batam City, in 2025. The case study was conducted from 12 to 18 August 2025. Nursing care implementation involved giving garlic water infusion every morning for seven consecutive days. The final evaluation showed a decrease in Mrs. J’s blood pressure from grade II hypertension to normal levels. This intervention is expected to enhance patient and family independence in continuing garlic water infusion therapy as a complementary approach to lowering blood pressure in elderly individuals with hypertension. Keywords: Hypertension, Garlic, Elderly